Позиція В. Філдермана щодо „єврейського питання” та його місця в політичному житті Румунії 1920–х років - Піддубний, Ігор (Chełm, Drukarnia Wydawnictwa ARKA, 2020)
The auther of article analyzes the publications and speeches of W. Filderman on the protection of the rights of the Jews of Romania. He opposed anti-Semitism and argued for the active participation of Jews in the development of Romania and the struggle for it. W. Fielderman was supported in such activities by members of the organization. In his work he relied on the principle of peace with the ruling nation and participation in the development of the country. Artykuł analizuje publikacje i przemówienia W. Fildermana na temat ochrony praw Żydów w Rumunii, który przeciwstawiał się antysemityzmowi i opowiadał się za aktywnym udziałem Żydów w rozwoju Rumunii i walce o nią. W. Fielderman był wspierany w takich działaniach przez członków organizacji. W swojej pracy opierał się na zasadzie pokoju z rządzącym narodem i udziale Żydów w rozwoju kraju.
Filderman’s position on the „Jewish question” and its place in the political life of Romania in the 1920-s
Stanowisko Fildermana w sprawie „kwestii żydowskiej” i jego miejsce w życiu politycznym Rumunii w latach dwudziestych XX wieku
Keywords: Румунія; єврейська громада; "єврейське питання"; В.Філдерман; міжвоєнний період; Союз євреїв Румунії